Bioactive ent-kaurane diterpenoids from Isodon serra. (October 2016) - Wan, Jun; Liu, Miao; Jiang, Hua-Yi; Yang, Jin; Du, Xue; Li, Xiao-Nian; Wang, Wei-Guang; Li, Yan; Pu, Jian-Xin; Sun, Han-Dong
Abstract: Nine 7, 20-epoxy- ent -kaurane diterpenoids (15-acetylmegathyrin B, serrin E, 14 β -hydroxyrabdocoestin A, serrin F, serrin G, 11- epi -rabdocoestin A, serrin H, serrin I, and 15-acetylenanderianin N), along with seven known ones, were isolated from the aerial parts of Isodon serra . Their structures were elucidated by extensive spectroscopic analysis, and the absolute configuration of 15-acetylmegathyrin B was determined by signal-crystal X-ray diffraction. All of these compounds were evaluated for their cytotoxic activities against five human tumor cell lines (HL-60, SMMC-7721, A-549, MCF-7, SW480). Serrin F, rabdocoestin B and 1 α, 11 β -dihydroxy-1 α, 11 β -acetonide-7 α, 20-epoxy- ent -kaur-16-en-15-one showed cytotoxic activities against all cell lines, with IC50 values ranging from 0.7 to 4.6 μ M; serrin F also strongly inhibited NO production in LPS-stimulated RAW264.7 cells. Otherwise, 14 β -hydroxyrabdocoestin A, serrins H and I, as well as enanderianin N and megathyrin B, also exhibited inhibitory effects towards NO production, while no cytotoxicity against five cell lines was detected. Graphical abstract: Nine diterpenoids were isolated from Isodon serra, together with seven previously known compounds. Three of them exhibited weak cytotoxicity against five tumor cell lines, and one strongly inhibited NO production. Highlights: Nine previously unknown and seven known ent -kaurane diterpenoids were obtained from Isodon serra. Cytotoxic and NO production inhibitory activities were evaluated. Three compounds showed weak cytotoxicity (IC50 values ranged from 0.7 to 4.6 μ M). Serrin F exhibited NO production inhibitory effect (IC50 = 0.6 μ M).